2006
DOI: 10.1523/jneurosci.2620-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

Stimulus Frequency Processing in Awake Rat Barrel Cortex

Abstract: In awake rats, we examined the relationship between neural spiking activity in primary somatic sensory cortex and the frequency of whisker stimulation. Neural responses were recorded extracellularly in barrel cortex while single whiskers were deflected with 0.5-18 air puffs per second (apps), a range that includes the whisk rates observed when rats explore their environment and discriminate surfaces with their whiskers. Twenty-nine neurons in layers III and IV were isolated in three rats (23 in barrel columns … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
28
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 75 publications
8
28
3
Order By: Relevance
“…IO stimulation at high intensity (20 and 30 Hz) resulted in no detectable activation of cortical neurons using c-Fos as a marker, a finding that correlated with the absence of tpO 2 dip and LFP responses, and the IO stimulation plots of synaptic activity with CBF and CMRO 2 displaying bell-shaped curves with very low responses at 30 Hz. They also agree with the reported decrement in the spiking rate of layers III and IV barrel neurons with increased stimulus frequency (Melzer et al, 2006). Our findings can well be explained by the frequency-dependent adaptation of cortical neurons, which occurs rapidly such that above 1 Hz, many cortical neurons cease firing after the first few deflections (Melzer et al, 2006).…”
Section: Discussionsupporting
confidence: 92%
“…IO stimulation at high intensity (20 and 30 Hz) resulted in no detectable activation of cortical neurons using c-Fos as a marker, a finding that correlated with the absence of tpO 2 dip and LFP responses, and the IO stimulation plots of synaptic activity with CBF and CMRO 2 displaying bell-shaped curves with very low responses at 30 Hz. They also agree with the reported decrement in the spiking rate of layers III and IV barrel neurons with increased stimulus frequency (Melzer et al, 2006). Our findings can well be explained by the frequency-dependent adaptation of cortical neurons, which occurs rapidly such that above 1 Hz, many cortical neurons cease firing after the first few deflections (Melzer et al, 2006).…”
Section: Discussionsupporting
confidence: 92%
“…As such, this procedure has enabled other difficult behavioral tasks (Gao et al, 2001;Bermejo et al, 2002;Gao et al, 2003b;Friedman et al, 2006) and intracellular (Crochet and Petersen, 2006) and extracellular (Sachdev et al, 2000;Kleinfeld et al, 2002;Melzer et al, 2006) recording studies. Yet it has been heretofore undocumented how head restraint may alter whisking behavior.…”
Section: Whisking In Head-fixed Versus Freely Exploring Animalsmentioning
confidence: 99%
“…During natural exploration and behavior, rodent whiskers often receive prolonged stimulation (Prigg et al, 2002;Knutsen et al, 2006), and the response properties of somatosensory cortical neurons to such stimulation are markedly different from those associated with brief, punctuate stimuli (Armstrong-James and Fox, 1987;Kleinfeld et al, 2002;Arabzadeh et al, 2004;Knutsen et al, 2006;Melzer et al, 2006). When we examined the effects of changes in cortical network activity on responses to continuous whisker stimulation, we found that cortical networks continued to alternate between Up-like states (i.e., periods of increased multiple-unit activity simultaneous with tonic intracellular depolarization and lasting 200 -1000 ms) and Down-like states (i.e., periods of decreased multiple-unit activity with tonic intracellular hyperpolarization) (supplemental Fig.…”
Section: Continuous Stimulationmentioning
confidence: 99%